CORPORATE GOVERNANCE TERHADAP MANDATORY DISCLOSURE IMPLEMENTASI KONVERGENSI IFRS - Ismunawan, Ismunawan; Triyanto, Eko (JAB (Jurnal Akuntansi & Bisnis), 2017)
The purpose of this research is to investigate the influence of corporate governance mechanisms to mandatory disclosure IFRS on companies listed on the Stock Exchange. Corporate governance mechanisms used in this study include: managerial ownership, institusional ownership, the proportion of independent board, the number of members of the audit committee, board of directors, and board meetings. The sample used in this research is manufacturing companies listed on the Stock Exchange in the year 2013-2015. The total sample is 102 companies were determined by purposive sampling method.These results indicate that the level of compliance with mandatory disclosure convergence of IFRS in the manufacturing companies is 54,89%.This study uses multiple regression analysis to examine the effect of corporate governance mechanisms to mandatory disclosure IFRS. The results of this study indicate that managerial ownership and institutional ownership has significant negative effect on mandatory disclosure IFRS, whereas commissioners significant positive effect on the mandatory disclosure IFRS. The variable proportion of independent board, the number of members of the audit committee and board meetings does not affect the mandatory disclosure IFRS.Â Keywords: Mandatory disclosure, corporate governance mechanisms